2012
DOI: 10.1128/jb.06747-11
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis RapA Phosphatase Domain Interaction with Its Substrate, Phosphorylated Spo0F, and Its Inhibitor, the PhrA Peptide

Abstract: Rap proteins in Bacillus subtilis regulate the phosphorylation level or the DNA-binding activity of response regulators such as Spo0F, involved in sporulation initiation, or ComA, regulating competence development. Rap proteins can be inhibited by specific peptides generated by the export-import processing pathway of the Phr proteins. Rap proteins have a modular organization comprising an amino-terminal alpha-helical domain connected to a domain formed by six tetratricopeptide repeats (TPR). In this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 41 publications
7
41
0
2
Order By: Relevance
“…6C and D). Substitution mutations at positions corresponding to RapP Asp203 were previously shown to render Rap proteins resistant to the inhibitory effects of their cognate Phr peptides (8,20,27,46). Moreover, we recently showed that B. subtilis Rap proteins have aspartate or, less commonly, glutamate at the position corresponding to RapP Asp203, and these conserved acidic residues form salt bridges with conserved basic residues in their cognate Phr peptides (47).…”
Section: Resultsmentioning
confidence: 99%
“…6C and D). Substitution mutations at positions corresponding to RapP Asp203 were previously shown to render Rap proteins resistant to the inhibitory effects of their cognate Phr peptides (8,20,27,46). Moreover, we recently showed that B. subtilis Rap proteins have aspartate or, less commonly, glutamate at the position corresponding to RapP Asp203, and these conserved acidic residues form salt bridges with conserved basic residues in their cognate Phr peptides (47).…”
Section: Resultsmentioning
confidence: 99%
“…The TPR domains, however, are conserved in comparison with PlcR and PrgX, and residues potentially involved in binding of the Phr peptides have already been identified. The role of a conserved asparagine has also been highlighted (26). Binding of Phr peptides thus most probably induces a conformational change that propagates from the TPR domain to the N-terminal domain interacting with the targeted protein.…”
Section: Discussionmentioning
confidence: 99%
“…RapA is a Spo0F phosphatase involved in the regulation of sporulation; PhrA is processed extracellularly to produce a pentapeptide that inhibits RapA activity (75). Therefore, CodY regulates the activity of RapA both at the level of rapA-phrA expression and at the level of Vpr-dependent proteolytic processing of the full-length PhrA protein.…”
Section: Discussionmentioning
confidence: 99%